Dissemination in Pigtailed Macaques after Primary Infection of Dengue-3 Virus - JOKO PAMUNGKAS; DIAH ISKANDRIATI; UUS SAEPULOH; MOSES AFFANDI; ESTHER ARIFIN; YASMINA PARAMASTRI; FITRIYA NUR ANISA DEWI; DONDIN SAJUTHI (Microbiology Indonesia, 2011)
Nonhuman primates (NHPs) play as indispensable animal model in biomedical research for studying a variety of human health issues, diseases and disorders, therapies, and preventive strategies. Since the immunological and physiological responses of NHPs, at some extent, to experimental viral infections are similar to humans, it is possible that studies of dengue infection in NHPs may aid understanding of dengue infection in humans. In this study,we used pigtailed macaques (Macaca nemestrina) as the experimental animal to study dengue-3 (DEN-3) virus infection.We evaluated DEN-3 viral distribution and replication sites after a primary infection in all collected tissues. Sequential localization in tissue of DEN-3 virus was studied in pigtailed macaques euthanized three days post viral inoculation (10 pfu mL ). Pigtailed macaque that was inoculated subcutaneously or intravenously; showed the highest viremia (62.94 pfu mL and 58.62 pfu mL ) detected by one step reverse transcription real time PCR. The virus inoculated in pigtailed macaques by subcutaneous injection was rapidly disseminated from the inoculation site to the lymph nodes, adrenal glands, kidneys, heart, thyroid, liver, prostate gland, and seminal vesicles. Meanwhile, dissemination of dengue virus in pigtailed macaques inoculated intravenously was detected in lymph nodes, thymus, salivary glands, liver, and prostate gland. This study suggested that the above mentioned-tissue specimens are involved or affected by DEN-3 virus replication and the route of infection seemed to have influenced the virus dissemination.